Analisis Metode Agregat Planning untuk Minimasi Biaya pada UMKM Makmur Jaya-Jakarta - Santika Sari; Dyah Ayu Pitaloka (Universitas Muhammadiyah Tangerang, 2022)
Aggregate planning is made to optimize the use of available labor and production equipment to formulate an overall plan to adjust production capacity in the face of uncertain market demands, so that total production costs can be minimized. This research was conducted to obtain the method used and to find a solution to reduce the cost of company expenses if the demand exceeds the total production capacity at UMKM Makmur Jaya, located in Lubang Buaya, East Jakarta. This research was conducted by comparing the two Forecasting methods,namely seasonal additiveand seasonalmultifikatif planningand compares the aggregate made by the method of Level Strategy, Chase strategy, and MixedStrategy.After conducting the research, the best method for forecasting was obtained, namely themethod Seasonal Additive with the smallest MAPE value of 0.2057. Then for the calculation of aggregate planning, a solution is found to reduce the cost of company expenses if the demand exceeds the total production capacity, you can use the method with themethod Level Strategy with a total cost of IDR 80,916,600.00 which is the lowest cost estimate for production planning for the next 12 months, with Total production planning is 4220 units and inventory is Final3839.